Erfassung von hitze- und feinstaubbedingten Gesundheitsrisiken in Deutschland: ein epidemiologischer Studienansatz - Georgy, Sascha; Lautenbach, Sven; Jahn, Heiko J.; Katzschner, Lutz; Krämer, Alexander (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
BackgroundExposure to heat and particulate matter is a cause of increased mortality. Climate change and increasing climate variability exacerbate these problems. Experts require assessments with which health risks and the success of preventative measures can be estimated. We implemented an ecological study approach to assess these risks at both small and large scales of reference levels (Federal Republic of Germany and territorial authority).MethodsWe utilised a case-crossover design to investigate the relationship between exposure and mortality. This study design uses a logistic regression model. Analogously to a matched case-control study, the odds ratio maps the effect strength. The study period included the years 2002-2006.ResultsThe analysis demonstrated health risks from exposure to heat for the German population (OR 1.1529, 95% CI 1.1517-1.1541; adjusted OR 1.0658). Significant evidence of a health risk was also documented for exposure to particulate matter (PM10; OR 1.2987, 95% CI 1.2951-1.3024; adjusted OR 1.0128). The risk does not significantly differ for women versus men; the variable age was also not significant at the level of the country-wide analysis, but for a few subordinate units of space.This study approach can be adapted for assessments at varying levels of reference and periods of time as well as for different populations.DiscussionThe methodological approach is useful for a reproducible study design. Nevertheless, other influencing factors such as ozone or PM2.5 should be incorporated in subsequent analyses to clarify whether these factors skew the results. Further analysis would also be useful to investigate if and to what extent socio-structural and socio-economic factors affect the associated risk.
Gesehen am 25.06.2019